Analysis of The Level of Financial Literacy of STIE Ganesha Students and Its Implications for Work Readiness (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study analyses the level of financial literacy of STIE Ganesha students and its impact on their readiness to face the world of work. Financial literacy encompasses the basic knowledge and skills of managing personal finances, which are essential for financial decision-making in a professional environment. Using a quantitative survey of 10 Management and Accounting students, the results show that most students have an adequate understanding of basic financial literacy, but their applicative skills in the work context still need to be improved. This study recommends strengthening the curriculum with a practical approach so that students are better prepared to face financial challenges in the world of work.